ANALYSIS OF ISLAMIC BANK FINANCIAL PERFORMANCE IN FACINGGLOBAL MARKET CHALLENGES - Novianty Djafri; Diah Fatma Sjoraida; Julinta Paulina; M. Anton Fatoni; Sudarmo (ADISAM Publisher, 2024)
This analysis evaluates the financial performance of Islamic Banks in facing global market challenges. The findings show that Islamic banks have demonstrated solid financial performance, with significant asset and revenue growth and effective risk management. Islamic banks have also managed to maintain good financing quality. However, Islamic banks face challenges in the global market, including intense competition with conventional banks, regulatory differences in various countries, and low customer awareness and education. To face this challenge, Islamic banks must improve operational efficiency, develop product and service innovations that suit customer preferences, strengthen marketing and branding, and expand distribution networks. This analysis concludes that Islamic banks have a strong potential to face global market challenges. With solid financial performance, significant asset growth, effective risk management, and adaptive strategies, Islamic banks can remain competitive in a dynamic global market. However, it is essential for Islamic banks to continuously monitor global market developments, manage risk appropriately, and strengthen their strategy to face the ever-evolving challenges.